2021
DOI: 10.12956/tchd.955627
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Pediatric Trauma Patients Requiring Pediatric Intensive Care Follow-up and Identifying the Differences in Refugee Children

Abstract: Objective: This study aimed to examine the causes and clinical course of trauma in trauma patients requiring pediatric intensive care unit (PICU) follow-up and evaluate possible differences related to demographic characteristics, trauma mechanism, trauma severity, and prognosis in refugee children. Material and Methods:The records of 175 patients admitted to our PICU between May 1, 2020 and April 30, 2021 with a preliminary diagnosis of trauma were retrospectively reviewed. The patients were divided into two g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In another study from our country by Emeksiz et al (22), it was shown that the most common cause of trauma was falling and all the patients who followed up had head trauma. In our study, 66.6% of trauma patients had head trauma and subdural hemorrhage was the most common finding in CT. As in previous studies, we would like to draw attention to the fact that head trauma due to falling is very common and affects mortality.…”
Section: Discussionmentioning
confidence: 90%
“…In another study from our country by Emeksiz et al (22), it was shown that the most common cause of trauma was falling and all the patients who followed up had head trauma. In our study, 66.6% of trauma patients had head trauma and subdural hemorrhage was the most common finding in CT. As in previous studies, we would like to draw attention to the fact that head trauma due to falling is very common and affects mortality.…”
Section: Discussionmentioning
confidence: 90%
“…Although the exact incidence of falls from great heights in children is not known in Türkiye, in a Turkish study it was demonstrated that the most common two causes of injury in the zero to four-yearold age group were burns and falls, and the most common cause of injury in the five to nine-year-old age group was falls (12). In a pediatric ICU study conducted in this hospital, 106 cases of falls from great heights were reported in one year (13).…”
Section: Discussionmentioning
confidence: 95%